1988
DOI: 10.1002/ajmg.1320300402
|View full text |Cite
|
Sign up to set email alerts
|

Activation of fatty acid oxidation in the Silver–Russell syndrome and the Brachmann–de Lange syndrome

Abstract: We describe a similar metabolic pattern of hyperketosis, ketonaciduria, and C6-C12 dicarboxylic aciduria in a patient with the Silver-Russell syndrome and a patient with the Brachmann-de Lange syndrome. Fasting blood levels of beta-hydroxybutyrate and acetoacetate were significantly higher than in age-matched controls, and both patients showed massive urinary excretion of beta-hydroxybutyrate, acetoacetate and C6-C12 dicarboxylic acids.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1991
1991
2005
2005

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Hemihypotrophy is not a symptom of the Floating-Harbor syndrome. Speech and mental development in cases with the Silver-Russell syndrome are either normal or slightly subnormal [5].…”
Section: Discussionmentioning
confidence: 99%
“…Hemihypotrophy is not a symptom of the Floating-Harbor syndrome. Speech and mental development in cases with the Silver-Russell syndrome are either normal or slightly subnormal [5].…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports in the literature suggest a spectrum of metabolic abnormalities, particularly hypoglycaemia. Willems et al in 1988 reported an RSS patient with ketoaciduria and dicarboxylic aciduria who had mild hypoglycaemia and ketosis. The following cases support the proposition that the RSS phenotype may be associated with several different metabolic errors.…”
Section: Metabolic Dysfunction In Russell-silver Syndromementioning
confidence: 99%
“…In addition, growth hormone (GH) insufficiency, previously documented in up to 60% of short children with intrauterine growth retardation (IUGR) as well as children with RSS 13 " 15 , could enhance the likelihood of the development of hypoglycaemia. Furthermore, some metabolic abnormalities during episodes of hypoglycaemia in children with RSS, such as ketoaciduria and dicarboxylic aciduria 16 , elevated serum long-chain fatty acids, increase in amino acids and lactate 6 , have been described. More recently, metabolic acidosis has been described as occurring more commonly in children with RSS 17 .…”
Section: Introductionmentioning
confidence: 98%